Assessing food safety knowledge and preferred information sources among 19–29 year olds. (November 2016) - Burke, Tangi; Young, Ian; Papadopoulos, Andrew
Abstract: Foodborne illness is a common and costly cause of gastroenteritis in Canada. Although high rates are expected in vulnerable populations, young adults experience a surprisingly high rate of foodborne illness. While research has indicated that young adults are undereducated in food safety, studies examining the knowledge of young Canadians, as well as approaches to improve their education, have not been conducted. An online questionnaire containing 33 questions was distributed to young adults in Canada via social media, questioning their food preparation knowledge, high risk activity knowledge, food safety information sources, and demographics. Of the 334 surveys completed, 307 were used to create the data set for this study. This study indicated that food safety knowledge in young Canadian adults (aged 19–29) is low. Common causes of foodborne illness were overlooked or not often recognized. For example, 4 °C – 60 °C was identified as an unsafe holding temperature by 41.0% of respondents; the safe internal temperature for chicken (74 °C) was identified by 38.8% of respondents. Multivariable logistic regression modeling indicated that food safety knowledge scores (proportion of questions answered correctly) were higher among females (OR = 1.20; 95% CI: 1.06, 1.37), those with previous food safety training (OR = 1.25; 95% CI: 1.09, 1.43), and those who indicated that they do not seek information about food safety from their family or friends (OR = 1.28; 95% CI: 1.12, 1.47). These results suggest the need for stronger, more targeted food safety education programs, aimed specifically at young adults. Although previous research indicated that social media may be a primary venue for education, most respondents did not desire to receive food safety information via social media at all. As such, food safety education programs targeted at this population will likely need to be multi-platform, and involve traditional and social media approaches. Highlights: Food safety knowledge in young Canadian adults (aged 19–29) is low. Common causes of foodborne illness are overlooked or not often recognized. There is a need for stronger, more targeted food safety education programs. Successful education programs will likely use multiple platforms.